Toxicities of Chimeric Antigen Receptor T Cell Therapy in Multiple Myeloma: An Overview of Experience From Clinical Trials, Pathophysiology, and Management Strategies - Zhou, Xiang; Rasche, Leo; Kortüm, K. Martin; Danhof, Sophia; Hudecek, Michael; Einsele, Hermann (Frontiers in Immunology, 2020)
In the last few years, monoclonal antibodies (mAbs) such as elotuzumab and daratutumab have brought the treatment of multiple myeloma (MM) into the new era of immunotherapy. More recently, chimeric antigen receptor (CAR) modified T cell, a novel cellular immunotherapy, has been developed for treatment of relapsed/refractory (RR) MM, and early phase clinical trials have shown promising efficacy of CAR T cell therapy. Many patients with end stage RRMM regard CAR T cell therapy as their “last chance” and a “hope of cure”. However, severe adverse events (AEs) and even toxic death related to CAR T cell therapy have been observed. The management of AEs related to CAR T cell therapy represents a new challenge, as the pathophysiology is not fully understood and there is still no well-established standard of management. With regard to CAR T cell associated toxicities in MM, in this review, we will provide an overview of experience from clinical trials, pathophysiology, and management strategies.